Gender Trouble Couplets, Volume 1 - Strouse, A.W (punctum books, 2019)
"Judith Butler's Gender Trouble: Feminism and the Subversion of Identity radically claimed that the sexed body is a fallacy, discursively constructed by the performance of gender. A.W. Strouse has undertaken to rewrite Butler's classic tome into an octosyllabic poem. Inspired by the rhyming encyclopedias of the Middle Ages, Strouse transforms each of Butler's sentences into Seussian couplets. This performative repetition of Chapter 1 of Butler's Gender Trouble, "Subjects of Sex/Gender/Desire," deconstructs Butler's deconstruction. Relishing in the campiness of rhyme and meter-in the bodily pleasures of form-Strouse's Gender Trouble Couplets, Volume 1 is an imitation for which there is no original. Gender Trouble, perhaps, was poetry all along."